Peran Keterampilan Kepemimpinan dalam Penerapan Keselamatan Pasien di Rumah Sakit : Systematic Literature review: Peran Keterampilan Kepemimpinan dalam Penerapan Keselamatan Pasien di Rumah Sakit : Systematic Literature review - AGUSTINA KURNIAWATI, NURUL; LAILIYAH, SYIFA'UL (Universitas Hang Tuah, 2023)
Background: The role of leadership in improving patient safety can encourage and guarantee the implementation of an integrated patient safety program in the organization through the implementation of seven steps towards hospital patient safety. The presence of leadership can ensure the ongoing proactive program for identifying patient safety risks. The leadership role of a leader is needed in implementing a patient safety culture.Objective: The aim of this research is to identify the role of leadership in implementing a hospital patient safety cultureMethod: The method used in writing this article is a literature review. Article searches were carried out via Google Scholar, Science direct and Pubmed. Publication years from 2019 to 2023 were then examined according to the researchers' inclusion criteria. Results: Based on the results of the literature review analysis, the role of leadership abilities has an impact on the implementation of patient safety culture in hospitals. The expected leadership skills are that the leader has empowering behavior, the leader is participatory, visionary and communicates effectively, the leader is able to direct staff effectively (directing), the leader has career support, psychosocial support and role modeling, the leader has an open and fair culture and Responsible leader. Conclusion: The use of leadership skills cannot be the same for all leaders. Because leaders have skills, leadership styles match their abilities. But leaders must know which leadership skills need to be used in dealing with conditions in the organization, especially in hospitals. The leadership role in improving patient safety can encourage and ensure the implementation of an integrated patient safety program Keywords: Leadership, Patient safety, Hospital